The influence of self-efficacy, achievement motivation, and scientific literacy on the effectiveness of educational practices - Rahmadi Budi Hartomo; Cepi Safruddin Abdul Jabar (Universitas PGRI Madiun, 2023)
This type of research is ex post facto research. The calculation of the sample size uses a table by Stephen Isaac, which is calculated by the Krecjie and Morgan formula (1970). From a sample of 330, a sample of 172 is needed (with a 5% error chance). Data analysis techniques are used using descriptive statistics and parametric statistics. The results of the analysis show that the effect of PLP 1 on microteaching, as seen in Pair 1, is 6.632 with a significance level of 0.000 (p value <0.05), then H0 is rejected and Ha is tested. The effect of microteaching on PLP 2 is seen in pair 2, where the t value is 1.126 with a significance level of 0.262 (p value> 0.05), then H0 is accepted. Ha is not tested. The effect of PLP 1 on educational practice is seen in pair 3, where the t value is 8.465 with a significance level of 0.000 (p value <0.05), then H0 is rejected and Ha is tested. The effect of microteaching on educational practice is seen in pair 4, where the t value is -4.287 with a significance level of 0.000 (p value <0.05), and H0 is rejected. Ha is tested. The effect of PLP 2 on educational practice is seen in pair 5, and the calculated t value is 10.749 with a significance level of 0.000 (p value <0.05), so H0 is rejected. The alternative hypothesis is tested.